Reversible Actuation Ability upon Light Stimulation of the Smart Systems with Controllably Grafted Graphene Oxide with Poly (Glycidyl Methacrylate) and PDMS Elastomer: Effect of Compatibility and Graphene Oxide Reduction on the Photo-Actuation Performance - Osicka, Josef; Mrlik, Miroslav; Ilcikova, Marketa; Hanulikova, Barbora; Urbanek, Pavel; Sedlacik, Michal; Mosnacek, Jaroslav (Polymers, 2018)
This study is focused on the controllable reduction of the graphene oxide (GO) during the surface-initiated atom transfer radical polymerization technique of glycidyl methacrylate (GMA). The successful modification was confirmed using TGA-FTIR analysis and TEM microscopy observation of the polymer shell. The simultaneous reduction of the GO particles was confirmed indirectly via TGA and directly via Raman spectroscopy and electrical conductivity investigations. Enhanced compatibility of the GO-PGMA particles with a polydimethylsiloxane (PDMS) elastomeric matrix was proven using contact angle measurements. Prepared composites were further investigated through the dielectric spectroscopy to provide information about the polymer chain mobility through the activation energy. Dynamic mechanical properties investigation showed an excellent mechanical response on the dynamic stimulation at a broad temperature range. Thermal conductivity evaluation also confirmed the further photo-actuation capability properties at light stimulation of various intensities and proved that composite material consisting of GO-PGMA particles provide systems with a significantly enhanced capability in comparison with neat GO as well as neat PDMS matrix.
Keywords: dielectrics; photo-responsive material; reduction; light-stimuli material; dynamic mechanical analysis; poly (glycidyl methacrylate); graphene oxide; SI-ATRP